Non vulgare genus: Ekphrasis, literarisches Gedächtnis und gattungsspezifische Innovation in der sechsten Ekloge des T. Calpurnius Siculus - Simon, L. Zoltán (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XLIII, 2007. At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.